2008
DOI: 10.1108/10610420810875052
|View full text |Cite
|
Sign up to set email alerts
|

The impact of culture on brand perceptions: a six‐nation study

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 20 publications
0
64
1
2
Order By: Relevance
“…The realized sample size with 722 respondents is comparable to research studies with similar scope (Esch et al 2006) or even exceeds these (Foscht et al 2008;Lee et al 2008).…”
Section: Data Collection and Sampling Proceduresmentioning
confidence: 67%
See 2 more Smart Citations
“…The realized sample size with 722 respondents is comparable to research studies with similar scope (Esch et al 2006) or even exceeds these (Foscht et al 2008;Lee et al 2008).…”
Section: Data Collection and Sampling Proceduresmentioning
confidence: 67%
“…The results of this research are also supported by the findings of other researchers. For instance Foscht et al (2008) using Aaker's brand personality dimensions found significant differences for the Red Bull brand personality across six different countries. Also, Hsieh (2002) found clusters of countries that share similar brand image perceptions among one cluster for car brands but different image perception in relation to a different cluster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In high power distance cultures, as in collectivist cultures (i.e., India), one's clothes, shoes, and posture define position in the social hierarchy, and external appearance is important to acquire respect from others . In addition, the greater pressure to conform to the in-groups that prevails in collectivist countries can affect consumer behavior, while members of individualist cultures are less likely to be pressured to buy brands that are not meaningful to them (Foscht et al, 2008). So, since sponsors can be considered in-group members, and there is a greater pressure to agree to the in-group when it comes to consumer behavior in collectivist cultures (Foscht et al, 2008;Gwinner, 2005), Indian sport fans have the potential for higher purchase intentions values than American and British sport fans.…”
Section: Purchase Intentionsmentioning
confidence: 99%
“…For example, respondents that are more educated can provide more accurate responses regarding purchase intentions (Sun & Morwitz, 2010). Moreover, considering national differences, in masculine cultures (i.e., the United States, the United Kingdom, and India) the decisions on larger purchases are usually made by males (Foscht, Maloles, Swoboda, Morschett, & Sinha, 2008), and, as a result, they can sustain higher purchase intentions across countries than females. Therefore, five demographic control variables (i.e., age, gender, education, household income and the household's decision maker) were also considered as they may influence the intensity of purchase intention across nations.…”
Section: Introductionmentioning
confidence: 99%